ABCB1 (P-glycoprotein) reduces bacterial attachment to human gastointestinal LS174T epithelial cells - Crowe, Andrew; Bebawy, M. (Elsevier Science, 2012)
The aim of this project was to show elevated P-glycoprotein (P-gp) expression decreasing bacterial association with LS174T human gastrointestinal cells, and that this effect could be reversed upon blocking functional P-gp efflux. Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Lactobacillus acidophilus and numerous strains of Escherichia coli, from commensal to enteropathogenic and enterohaemorrhagic strains (O157:H7) were fluorescently labelled and incubated on LS174T cultures either with or without P-gp amplification using rifampicin. PSC-833 was used as a potent functional P-gp blocking agent. Staphylococcus and Pseudomonas displayed the greatest association with the LS174T cells. Surprisingly, lactobacilli retained more fluorescence than enteropathogenic -E. coli in this system. Irrespective of attachment differences between the bacterial species, the increase in P-gp protein expression decreased bacterial fluorescence by 25–30%. This included the GFP-labelled E. coli, and enterohaemorrhagic E. coli (O157:H7). Blocking P-gp function through the co-administration of PSC-833 increased the amount of bacteria associated with P-gp expressing LS174T cells back to control levels. As most bacteria were affected to the same degree, irrespective of pathogenicity, it is unlikely that P-gp has a direct influence on adhesion of bacteria, and instead P-gp may be playing an indirect role by secreting a bank of endogenous factors or changing the local environment to one less suited to bacterial growth in general.